The Gamma Gap and All-Cause Mortality - Juraschek, Stephen P. (PLoS One, 2015)
BACKGROUND: The difference between total serum protein and albumin, i.e. the gamma gap, is a frequently used clinical screening measure for both latent infection and malignancy. However, there are no studies defining a positive gamma gap. Further, whether it is an independent risk factor of mortality is unknown. METHODS AND FINDINGS: This study examined the association between gamma gap, all-cause mortality, and specific causes of death (cardiovascular, cancer, pulmonary, or other) in 12,260 participants of the National Health and Nutrition Examination Survey (NHANES) from 1999–2004. Participants had a comprehensive metabolic panel measured, which was linked with vital status data from the National Death Index. Cause of death was based on ICD10 codes from death certificates. Analyses were performed with Cox proportional hazards models adjusted for mortality risk factors. The mean (SE) age was 46 (0.3) years and the mean gamma gap was 3.0 (0.01) g/dl. The population was 52% women and 10% black. During a median follow-up period of 4.8 years (IQR: 3.3 to 6.2 years), there were 723 deaths. The unadjusted 5-year cumulative incidences across quartiles of the gamma gap (1.7–2.7, 2.8–3.0, 3.1–3.2, and 3.3–7.9 g/dl) were 5.7%, 4.2%, 5.5%, and 7.8%. After adjustment for risk factors, participants with a gamma gap of ≥3.1 g/dl had a 30% higher risk of death compared to participants with a gamma gap <3.1 g/dl (HR: 1.30; 95%CI: 1.08, 1.55; P = 0.006). Gamma gap (per 1.0 g/dl) was most strongly associated with death from pulmonary causes (HR 2.22; 95%CI: 1.19, 4.17; P = 0.01). CONCLUSIONS: The gamma gap is an independent risk factor for all-cause mortality at values as low as 3.1 g/dl (in contrast to the traditional definition of 4.0 g/dl), and is strongly associated with death from pulmonary causes. Future studies should examine the biologic pathways underlying these associations.